Impact of income inequality on emigration: case of Lithuania and other new EU member states - Laurinavičius, Algimantas; Laurinavičius, Antanas; Laurinavičius, Alfredas (Business, Management and Economics Engineering, 2020)
Purpose – The objective of the article is to analyse how income inequality affects population decisions on emigration. Research methodology – Correlation and regression analysis are used to determine the relationship between the analysed social phenomena. Firstly, the correlation between income inequality (its change) and emigration rates is calculated. Secondly, the static and dynamic aspect is evaluated, as well as the influence of data delay (lag) on decision-making. Finally, a regression equation is constructed, showing how one variable affects the other. Findings – The analysis identifies the conditions and severity of population income inequality that may influence their emigration decisions. On the one hand, the impact is more substantial in the crisis and post-crisis period, and, on the other, in the new EU member states. Research limitations – Sensibility of emigration to different conditions like accessibility (i.e. the opportunity to emigrate freely, such as being a member of the Schengen area) and the income gap between countries of origin and destination is a major limitation of the article which should be examined more closely in later works. Practical implications – The analysis of emigration problem and the identification of its possible links with income inequality would allow economists to assess a priori potential of various measures suggested in practice and, consequently, would allow for the more targeted formulation of the State economic policy. Originality/Value – The novelty of the article is defined by insufficient scientific research of relationships between income inequality and emigration as socio-economic phenomena within the new EU member states. A scientific analysis of the problem of emigration and the identification of its possible links with income inequality would contribute to a more detailed study of the scientific aspects of emigration and income inequality.